Slow Dynamics of Premelting Water Molecules Confined in a Hydrophilic Nanoporous Space. Issue 21 (6th June 2019) - Ohata, Yuki; Kamebuchi, Hajime; Watanabe, Keisuke; Kouchi, Takaya; Suzuki, You; Imaizumi, Taku; Sugaya, Tomoaki; Mizuno, Motohiro; Tadokoro, Makoto
Abstract: The mobility, thermal behaviour, and crystal structures of water molecules confined within a one‐dimensional (1‐D), nanoporous single crystal in the premelting state were investigated in this study. Water clusters confined within the hydrophilic crystal revealed a premelting phase that was intermediate between the frozen and melted states. Water molecules in the premelting phase moved slowly. Heat capacity measurements showed that this motion could continue for approximately 24 hours after annealing at 160 K, although this could not be confirmed with solid‐state 2 H‐NMR analysis. X‐ray diffraction analysis established the coexistence of crystal structures in the frozen and premelting states at 165 K. These results represent a valuable contribution to understanding the dynamic properties of water confined within nanoscale spaces. Abstract : Premelting ice structure: This study investigated the mobility, thermal behaviour, and crystal structures of water molecules confined within a 1‐D nanoporous single crystal in the premelting state. The water clusters that was confined within the hydrophilic, one‐dimensional nano‐porous crystal revealed a premelting phase that was an intermediate between a freezing and a melting state.